PENGEMBANGAN KEILMUAN DAKWAH UNTUK MASYARAKAT AGAMA - Salmadanis Salmadanis (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The existence of the Da'wah Faculty of attendance is certainly to answer the problems that exist in the community grow and develop during the time someone or a group of people have completed their education at this institution. There are several functions of the Da'wah faculty that are relevant to the progress of a nation and state, namely preparing someone or a group of people to be skilled in a job needed by a community in accelerating development; as a means of transmitting the values of life incarnated in positive attitudes that will strengthen the image and culture of the nation, and a high attitude towards nationality; as a forum to strengthen the social role as agents of change; as a reliable provider of da'wah power that can accelerate the country's development; and so forth.